2006
DOI: 10.1088/0957-4484/17/20/010
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of highly ordered nanoporous alumina films by stable high-field anodization

Abstract: Stable high-field anodization (1500–4000 A m−2) for the fabrication of highly ordered porous anodic alumina films has been realized in a H3PO4–H2O–C2H5OH system. By maintaining the self-ordering voltage and adjusting the anodizing current density, high-quality self-ordered alumina films with a controllable inter-pore distance over a large range are achieved. The high anodizing current densities lead to high-speed film growth (4–10 µm min−1). The inter-pore distance is not solely dependent on the anodizing vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(167 citation statements)
references
References 17 publications
4
159
0
1
Order By: Relevance
“…The Joule's heat generated from the specimen during hard anodizing is effectively removed using a heat sink on the back side of the specimen. The hard anodizing allows the fabrication of a self-ordered porous oxide with various cell diameters under high voltage conditions: sulfuric acid at 27-80 V to 72-145 nm [104], oxalic acid at 120-150 V to 220-300 nm [105], and phosphoric acid at 195 V to 320-380 nm [106]. In addition, several research groups have reported using the advanced hard anodizing technique to further extend the self-ordering voltage and the corresponding cell diameters [107][108][109][110][111].…”
Section: Fabrication Of Highly Ordered Porous Aluminum Oxidementioning
confidence: 99%
“…The Joule's heat generated from the specimen during hard anodizing is effectively removed using a heat sink on the back side of the specimen. The hard anodizing allows the fabrication of a self-ordered porous oxide with various cell diameters under high voltage conditions: sulfuric acid at 27-80 V to 72-145 nm [104], oxalic acid at 120-150 V to 220-300 nm [105], and phosphoric acid at 195 V to 320-380 nm [106]. In addition, several research groups have reported using the advanced hard anodizing technique to further extend the self-ordering voltage and the corresponding cell diameters [107][108][109][110][111].…”
Section: Fabrication Of Highly Ordered Porous Aluminum Oxidementioning
confidence: 99%
“…We also added alcohol to the aqueous solution to tune the ionic conductivity in the pores. [ 19,21,42 ] The preformed oxide layer can be grown using a pre-anodization step carried out under mild conditions, which are stable from the beginning. Phosphoric acid anodization at low voltages can serve this purpose.…”
Section: The Plot Inmentioning
confidence: 99%
“…12,13 In particular, PAA has become increasingly important in biomedical applications over the past years because of its chemical stability as well as orthopedic biomimetic and biologicallyinspired properties. [14][15][16][17][18][19] Recently, Wang et al and Hu et al studied NIH 3T3 (fibroblasts) and PC12 (pheochromocytoma) cellular behaviors on PAA with different pore sizes, but the nanopore arrays used in their study were in a disordered arrangement and pore size distribution was not even.…”
Section: Introductionmentioning
confidence: 99%